2018
DOI: 10.1155/2018/4273107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combination of Prednisone or Mycophenolate Mofetil and Mesenchymal Stem Cells on Lupus Symptoms in MRL.Faslpr Mice

Abstract: The combination of immunosuppressants and mesenchymal stem cells (MSCs) is a promising therapeutic strategy for systemic lupus erythematosus, since this approach reduces doses of immunosuppressants while maintaining the same therapeutic outcome. However, it is unavoidable for MSCs to be exposed to immunosuppressants. Here, we examined the combination effect of prednisone (PD) or mycophenolate mofetil (MMF) and MSCs. We showed that PD or MMF in combination with MSCs showed better therapeutic effect than single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Lee et al [14] showed that the transfer of hMSCs increased MRL.Fas lpr mouse survival, decreased T cell infiltration in the kidneys, and reduced T cell cytokine expression. Lee et al [24] also showed that hMSCs in combination with prednisone or mycophenolate mofetil had a better therapeutic effect than single therapy in MRL.Fas lpr mice; the following readouts were used in this study: prolongation of survival, decrease in anti-dsDNA and total IgG levels in serum, decrease in cytokine gene expression in spleen cells, and decrease in inflammatory cell infiltration into the kidney. Liu et al [25] showed that hMSCs reduced proteinuria level, serum anti-dsDNA antibody level, and renal damage in MRL.Fas lpr mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [14] showed that the transfer of hMSCs increased MRL.Fas lpr mouse survival, decreased T cell infiltration in the kidneys, and reduced T cell cytokine expression. Lee et al [24] also showed that hMSCs in combination with prednisone or mycophenolate mofetil had a better therapeutic effect than single therapy in MRL.Fas lpr mice; the following readouts were used in this study: prolongation of survival, decrease in anti-dsDNA and total IgG levels in serum, decrease in cytokine gene expression in spleen cells, and decrease in inflammatory cell infiltration into the kidney. Liu et al [25] showed that hMSCs reduced proteinuria level, serum anti-dsDNA antibody level, and renal damage in MRL.Fas lpr mice.…”
Section: Discussionmentioning
confidence: 99%
“…To measure B cell proliferation, cells were pulsed with [ 3 H]-thymidine (113 Ci/nmol; NEN, Boston, MA, USA) at a concentration of 1 μCi/well for the last 18 h and were harvested on day 3 using an automated cell harvester (Inotech, Dottikon, Switzerland). The amount of [ 3 H]-thymidine incorporated into the cells was measured using a Wallac Microbeta scintillation counter (Wallac, Turku, Finland) 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent adult stem cells that have emerged as a promising therapy for the treatment of SLE. Adoptive transfer of MSCs to lupus-prone MRL .Fas lpr mice increased their survival and decreased anti-dsDNA antibody level and nephritis 3 - 9 . In clinical studies, MSCs improved renal functions and decreased autoantibody production 10 - 15 .…”
Section: Introductionmentioning
confidence: 96%
“…Whole cell lysates were prepared as previously described (23). Detergent-insoluble material was removed, and equal amounts of protein were fractionated by 10% SDS-PAGE and transferred to pure nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%